Effect of Clopidogrel Use Post Coronary Artery Bypass Surgery on Graft Patency - Ebrahimi, Ramin; Bakaeen, Faisal G.; Uberoi, Abhimanyu; Ardehali, Abbas; Baltz, Janet H.; Hattler, Brack; Almassi, G. Hossein; Wagner, Todd H.; Collins, Joseph F.; Grover, Frederick L.; Shroyer, A. Laurie (The Annals of thoracic surgery, 2014)
Clopidogrel use post coronary artery bypass grafting (CABG) has become more popular under the assumption that it improves graft patency. The purpose of this sub-analysis from the Randomized On and Off-Pump Bypass (ROOBY) trial is to evaluate the role of clopidogrel use post CABG to improve graft patency when added to standard aspirin therapy. The ROOBY trial was a multi-center, randomized, controlled clinical trial that compared on-pump versus off-pump coronary artery bypass grafting (CABG). Clopidogrel use post CABG was left at the discretion of the operator. Detailed data regarding the use and timing of clopidogrel post CABG were collected prospectively, along with 1-year angiograms to evaluate graft status. Of the 2,203 subjects undergoing CABG, 953 patient records had complete clopidogrel use and 1-year angiographic data. Of these, 345 (36.2%) received clopidogrel post CABG prior to discharge. Compared with patients with no post-CABG clopidogrel use, baseline characteristics were similar for the clopidogrel group except for the following: lower preoperative aspirin use (80.2% vs 86.7%, p = 0.009); higher preoperative clopidogrel use (23.5% vs 14.0%, p < 0.001), less on-pump (35.9% vs 55.9%, p < 0.0001); and lower endoscopic vein harvesting (30.8% vs 42.5%, p < 0.001) rates. Overall 1-year graft patency rates were not different between the clopidogrel and no-clopidogrel groups (86.5% vs 85.3%, p = 0.43). Multivariable analyses did not alter these findings. This study suggests that routine post-CABG clopidogrel use may not translate to improved 1-year graft patency. Future studies appear warranted to better define the role of more aggressive antiplatelet therapy post CABG on graft patency and clinical outcomes.